Pattern-Oriented Analysis and Design : Composing Patterns to Design Software Systems - Ammar, Hany; Yacoub, Sherif (Addison-Wesley Professional, 2003)
Design patterns are immensely powerful, but to build large-scale robust systems, you need more. Pattern-Oriented Analysis and Design introduces a methodology for "composing" proven design patterns into reliable, robust large-scale software systems. Using POAD, you can quickly build systems that are far more robust, scalable, and maintainable-using UML class diagrams as your building blocks. POAD: What it is, how it works, and what problems it solves Structural and behavioral approaches to design pattern composition Design models and UML techniques for pattern composition POAD processes: in depth coverage of analysis, design, and design refinement A systematic process to compose design patterns 4 chapter-length case studies: feedback control, customer behavior simulation, digital content processing, and distributed medical informatics Building on POAD: advanced trends and research Pattern-Oriented Analysis and Design takes design patterns to the next level. Whether you're an architect, designer, developer, or manager, it will help you build better software systems faster.